A gestão da cidade sustentável: com criatividade fazendo mais com menos recursos - Lopes, Gilson Eduardo Kurtz de Carvalho (2013)
This work presents a short study on creativity in Public Management Council. Will discuss topics such as sustainability, leadership, governance. We present a scenario of what happens today in small municipalities with the loss of the personality of the cities on account of canned programs and projects that are increasingly available to managers accommodated within your comfort zone. Show several examples that can be followed by managers willing to transform the reality of their municipalities, which promote the participation of their communities in the decisions and directions are followed and also know how to work with social control in their favor.